Building the Foundation of Education through Learning Philosophy and Theory: A Study on Strengthening the Educational Function of Libraries - Alamin, Rahmatan Lil; Febriyanti, Adelia Putri; Firmansyah, Eka (Journal of English Language and Education, 2026)
Quality education requires a solid philosophical and theoretical foundation. Educational philosophy provides the normative direction and values of education, while learning theories offer empirical guidance for designing effective and learner-centered instruction. This study examines how both perspectives strengthen educational foundations through optimizing the educational role of libraries in the digital era. Using a descriptive qualitative literature review supported by findings from the Darul Ma’arif Al Insan Foundation, the study reveals that philosophy shapes educational orientation, whereas learning theories guide practical instructional strategies. Their integration reinforces libraries as active learning centers that promote information literacy, character development, independent learning, and lifelong learning. Libraries managed in alignment with philosophical principles and learning theories—through relevant collections, adaptive services, and supportive environments—can enhance their function as non-formal educational institutions. Thus, educational philosophy and learning theories are strategic components in building an adaptive and sustainable education system in the context of digital transformation.